Waste less time on Facebook — follow Brilliant.
×

Prove this

\[ \large\dfrac1{2^m} \sum_{k=1}^{2^m} \dfrac{f(k)} k > \dfrac23. \]

Let \(f(n)\) be the greatest odd divisor of \(n\). Prove that for all positive integers \(m\), the inequality above holds true.

Note by Yash Saxena
1 year, 11 months ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

Induct on \(m\); this is obvious for \(m = 1\). Assume this is true for \(m = M\), and we will prove this for \(m = M+1\).

Note that \(f(k) = f(2k)\) and \(f(2k-1) = 2k-1\). Thus,

\[\begin{align*} \frac{1}{2^{M+1}} \sum_{k=1}^{2^{M+1}} \frac{f(k)}{k} &= \frac{1}{2^{M+1}} \sum_{k=1}^{2^M} \left( \frac{f(2k-1)}{2k-1} + \frac{f(2k)}{2k} \right) \\ &= \frac{1}{2^{M+1}} \sum_{k=1}^{2^M} \left( \frac{2k-1}{2k-1} + \frac{f(k)}{2k} \right) \\ &= \frac{1}{2^{M+1}} \sum_{k=1}^{2^M} \left( 1 + \frac{1}{2} \cdot \frac{f(k)}{k} \right) \\ &= \frac{1}{2^{M+1}} \sum_{k=1}^{2^M} 1 + \frac{1}{2^{M+1}} \sum_{k=1}^{2^M} \frac{1}{2} \cdot \frac{f(k)}{k} \\ &= \frac{1}{2^{M+1}} \cdot 2^M + \frac{1}{2^{M+2}} \sum_{k=1}^{2^M} \frac{f(k)}{k} \\ &> \frac{1}{2} + \frac{1}{4} \cdot \frac{2}{3} \\ &= \frac{2}{3} \end{align*}\]

In the first equality, we unroll the summation so we're summing two terms at a time. The second equality uses the aforementioned facts \(f(k) = f(2k)\) and \(f(2k-1) = 2k-1\). The rest should be fairly straightforward; the inequality invokes the inductive hypothesis.

This completes the proof for \(m = M+1\), and thus finishes the proof by induction.

Ivan Koswara - 1 year, 11 months ago

Log in to reply

Was writing up a proof, but your method is surely more elegant. Well done!

Jake Lai - 1 year, 11 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...